Pengaruh Kompetensi dan Kurikulum terhadap Kualitas Lulusan dengan Pelatihan sebagai Variabel Intervening - Munawir, Rahmad; Elfiswandi; Lusiana (SAFE-Network, 2024)
The aim of this research is to test how much influence Competency and Curriculum have on the Quality of Graduates with Intervening variable training at the Darussalam Pinagar Islamic Boarding School, West Pasaman Regency. The data collection method is through surveys and distributing questionnaires, with a sample of 100 respondents. The analysis method used is path analysis using SMARTPLS 3. The research results show that competency has a positive and significant effect on training. The curriculum has a positive and significant effect on training. Competency has an insignificant positive effect on the quality of graduates. The curriculum has a positive and significant effect on the quality of graduates. Training does not have a positive and significant effect on the quality of graduates. Training does not mediate the influence of competency on the quality of graduates. Training does not mediate the influence of the curriculum on the quality of graduates. The contribution of the independent variables Competency, Curriculum and Training to the dependent variable Graduate Quality is 81.8%. Meanwhile, the remaining 18.2% is influenced by other variables outside this research.